Establishing the character and share of changes in nutrients during the production of bread with the addition of dog rose syrup - Omarov, Yashar; Bayramov, Eldaniz; Haciyeva, Aygun; Gurbanova, Sevda; Aslanova, Mehriban; İsmayılov, Mehman; Nabiyev, Ahad (Eastern-European Journal of Enterprise Technologies, 2024)
In the daily diet, bread is an excellent carrier of nutrients to replenish the body. In this direction, as an additive, dog rose syrup (DRS) can be indispensable for the production of a wide range of bakery products. One of the factors limiting the widespread use of DRS in baking production is the insufficient knowledge of its biological value and changes in the share of nutrients in the technological process. Therefore, the purpose of the study is to analyze the nutritional value, vitamin and mineral composition of wheat flour “Azamatli-95” of the first grade (A95WF), DRS from the variety “R.canina”, and bread with the addition of DRS. It was found that with the addition of 5, 10 and 15 % DRS to A95WF in bread samples, the content in g/100 g significantly increases: glucose (0.09±0.05), fructose (0.15±0.08), sucrose (0.02±0.01) and phenolic compounds (0.38±0.1); in mg/100 g: beta-carotene (0.152±0.076), vitamin C (33.6±16.3), potassium (40.07±20.03), magnesium (36.49±18.25), phosphorus (20.94±10.47); in µg/100 g: iron (128.86±64.43) and zinc (18.95±9.47) and the content in g/100 g slightly increases: starch, proteins and raffinose (0.01±0.01), cellulose (0.04±0.02), pectin substances (0.03±0.01); in mg/100 g: thiamine (0.006±0.003), riboflavin (0.013±0.006), niacin (0.015±0.008), calcium (5.39±2.7), sodium (1.25±0.62), sulfur (5.99±2.99); in µg/100 g: iodine (0.42±0.21), cobalt (0.62±0.31) with deviation from the best bread with the addition of 10 % DRS to A95WF. The resulting regression equations (АЕ<7 %) make it possible to predict and establish a relationship between the shares of changes in significantly changing nutrients, vitamins and minerals in the technological process and the increase in their content in bread